PENGEMBANGAN PAKET WISATA OUTBOUND DI DESA WISATA HIJAU BILEBANTE LOMBOK TENGAH - Ela Ardiana Safitri; Supardi, Supardi; Rumba, Rumba (Bajang Institute, 2024)
Outbound Tour Packages are packages that provide tourist facilities for tourists to visit a destination and carry out all kindsof fun activitiesin the form of outbound activities. This research was motivated by the author’s desire to see innovation in outbound tourism packages in the Bilebante Green Tourism Village, Pringgarata District, Central Lombok Regency. The aim of this research is to find out how to develop outbound tourism packages in the Bilebante Green Tourism Village. The empowerment of women and high solidarity from the community was the beginning of the development of the Bilebante Green Tourism Village. The research method used in this research is a desciptive qualitative method. The data collection stages were carried out throught observation, interviews and documentation stages and the result of this research were the discovery of the advantages and disadvantages of the Outbound Tour Package in the Bilebante Green Tourism Village which the researchers innovated into an Outbound Tour Package in the form of a Flyer Tour Packages